2019
DOI: 10.1155/2019/4365358
|View full text |Cite
|
Sign up to set email alerts
|

Explore Knowledge‐Sharing Strategy and Evolutionary Mechanism for Integrated Project Team Based on Evolutionary Game Model

Abstract: Integrated Project Delivery (IPD) has become increasingly popular in the architecture, engineering, and construction industries. However, the current practice status by the construction industry fails to deliver the desired results. In that backdrop, how to promote cooperation within and improve the overall performance of integrated project team has received wide attention. Herein, knowledge-sharing plays a critical role in cooperation and overall performance. However, to the best of our knowledge, the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 112 publications
(90 reference statements)
1
11
0
Order By: Relevance
“…If det(J) > 0 and tr(J) = 0, the point is defined as a central point. Additionally, if det(J) < 0, the point is defined as a saddle point [ 40 ]. As shown in Table 3 , the existence of evolutionary stable points (ESS) in the model requires comparing α, β, γ, δ.…”
Section: Discussionmentioning
confidence: 99%
“…If det(J) > 0 and tr(J) = 0, the point is defined as a central point. Additionally, if det(J) < 0, the point is defined as a saddle point [ 40 ]. As shown in Table 3 , the existence of evolutionary stable points (ESS) in the model requires comparing α, β, γ, δ.…”
Section: Discussionmentioning
confidence: 99%
“…There is an extraordinary amount of in-depth literature regarding collaborative project delivery models. In IPD scholarship alone there are numerous examples of comparative case studies (Ballard et al, 2015; Cheng et al, 2012, 2016; Cohen, 2010; Denerolle, 2013); management strategies (Fischer et al, 2017); impact on desirable project characteristics, such as trust, innovation, and supply chain collaboration (Hall et al, 2018; Lavikka et al, 2015; Pishdad-Bozorgi & Beliveau, 2016; Zhang et al, 2020); quantifications of IPD project outcomes compared to other types of project delivery methods (El Asmar et al, 2013, 2016; Franz et al, 2017; Mesa et al, 2016); and theorizations of ideal IPD profit pool distributions using cooperative game theory (Du et al, 2019; Teng et al, 2019). As Ostrom noted in her own scholarship on common-pool resource scenarios, such literature holds rich accounts and models developed by field researchers who have invested years of effort to obtain detailed information about the strategies adopted by appropriators (Ostrom, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that mutual trust, property rights protection, and corporate culture integration can promote knowledge-sharing behaviors. In a similar study, Du et al [42] pointed out that the factors that affect team knowledge sharing include knowledge stock, knowledge ratio, knowledge absorption coefficient, synergy coefficient, and knowledge-sharing cost.…”
Section: Knowledge Sharing As An Evolutionary Gamementioning
confidence: 99%